Importance of Sensitive Vascular Measurements for Evaluating Effects of Lifestyle in Premenopausal Women - Lane-Cordova, Abbi D.; Bouknight, Samantha (Frontiers in Cardiovascular Medicine, 2020)
Premenopausal women generally have a favorable cardiovascular risk profile, owing to young age and the protective effects of estrogen. Rates of hypertension and more advanced cardiovascular disease (CVD) are low in premenopausal women. A large body of epidemiological evidence has shown that lifestyle behaviors in midlife, i.e., cardiorespiratory fitness, physical activity, and healthy diet, are associated with lower risk of overt CVD and adverse cardiovascular outcomes in the future for men and women. Despite differences in future cardiovascular risk, brachial blood pressures might be similar between premenopausal women with favorable vs. unfavorable levels of lifestyle behaviors in early-to-mid-life. Here we make the case for deeper phenotyping by means of vascular function measurements, such as arterial stiffness, augmentation index, and endothelial function, to identify potential mechanistic pathways linking lifestyle behaviors in early-to-mid-adulthood with lifelong CVD risk in women. We describe considerations for vascular function measurement in premenopausal women and opportunities for investigators to fill in knowledge gaps to further our understanding of CVD risk assessment and CVD progression in premenopausal women.